The Development of the Measure of Adolescent Relationship Harassment and Abuse (MARSHA): Input From Black and Multiracial, Latinx, Native American, and LGBTQ+ Youth. Issue 5 (March 2022) - Rothman, Emily F.; Paruk, Jennifer; Cuevas, Carlos A.; Temple, Jeff R.; Gonzales, Kelly
This formative research study was designed to collect opinion data from adolescents historically underrepresented in adolescent dating abuse (ADA) research measure development. Eight in-person focus groups and 7 telephone-based one-on-one interviews were conducted with U.S. youth aged from 11 to 20 years ( N =48). We conducted two focus groups with Black, Multiracial, Latinx, Native American, and LGBTQ+ youth. Seven LGBTQ+ youth participated in one-on-one telephone-based interviews. Focus group participants and interview subjects were asked the same 11 questions from a semi-structured focus group question guide. Five questions were on the topic of dating behaviors in general. In addition, six questions were asked for reactions to a paper-based list of 75 abusive acts. Youth generated ideas for 10 new possible cyber-ADA items and 14 emotionally abusive items for inclusion on the ADA measurement instrument. They did not generate any new physical or sexual ADA items. Youth identified 14 acts that they felt should not be on the measure, either because the acts were not abusive and too common, because they could not understand the item, or because it seemed unrealistic as an act of ADA. The study faced several limitations and was a good first step toward enriching the cultural inclusivity of ADA measurement instrument. Continued attention to inclusionary research that seeks to understand the cultural milieux of diverse participants is essential for violence prevention scholarship and subsequent health programming and policy that derive from it.